Utility of telemetry in syncope admissions. (14th October 2021) - Saha, T; Bagel, P; Toole, J; Coplan, N
Abstract: Introduction: Syncope is a major cause of emergency room visits and admission to telemetry units however, prior studies have shown conflicting evidence for the necessity for a telemetry admission. Our current 2017 ACC/AHA/HRS guidelines recommend telemetry admissions for syncope evaluation when cardiac etiology is suspected. Purpose: The purpose of this study is to investigate whether there are any differences in telemetry events in patients with a cardiac syncope versus non-cardiac/unspecified and to determine any correlation between the number of cardiac risk factors in patients with cardiac syncope versus non-cardiac etiology to predict those who would benefit most from telemetry. Methods: Our retrospective study included 574 patients admitted to the cardiac telemetry unit between February 2017 and February 2020 at our metropolitan tertiary care centre, further grouped into: cardiac, non-cardiac, or unspecified syncope. Cardiac syncope included aetiologies such as arrhythmias, pulmonary hypertension, Long QTc, device malfunction etc. The non-cardiac syncope group included aetiologies such as orthostatic and reflex mediated. Thirteen cardiac risk factors were summed from the 2009 ESC syncope guidelines. These included HFrEF, elevated BNP, anemia, abnormal ECG, family history of sudden cardiac death or MI, age above 65, male gender, structural heart disease, abnormal vitals on presentation, history of sudden cardiac death, no prodrome prior to syncope and chest pain. Results: Of the 574 patients, 102 patients (17.7%) had a cardiac etiology, 405 patients (70.5%) had a non-cardiac etiology and 67 patients (11.6%) had unspecified etiology for syncope. Overall, 47% of the cardiac group, 16% of the non-cardiac group, and 12% of the unspecified group had telemetry events. There was a statistically significant difference in the number of patients with telemetry events among the three syncope groups, p<0.0001. The odds of patients with cardiac syncope having telemetry events were 4.0 times greater than those with non-cardiac syncope and 6.3 time higher than those with unspecified syncope. The average number of risk factors were: 4 (±1.7) (cardiac), 3±1.6 (non-cardiac), and 3±1.7 (unspecified). Linear regression model showed the number of risk factors to be 19% and 15% lower in the non-cardiac and unspecified groups compared to the cardiac group. There was no association between any of the individual risk factors and the presence of telemetry event. Conclusions: Our study demonstrates that those with cardiac syncope tend to have more cardiac risk factors and more telemetry events relative to their non-cardiac syncope counterparts. While patients with cardiac risk factors have on average a higher cardiac risk factor profile, it is not clinically significant enough to determine who would benefit from telemetry versus who would not. Funding Acknowledgement: Type of funding sources: None.